FIRST FOND OF TITANIUM NITRIDE (OSBORNITE) IN TERRESTRIAL ROCKS - Tatarintsev V.I.; Sandomirskaya S.M.; Tsymbal S.N. (My University, 1987)
In 1984 the authors detected corundum grains with titanium nitride inclusions in samples of compositionally complex Upper Devonian breccias and Quaternary deposits, collected near the junction of the Azov block with the Donbas. These breccias constitute a pipe-shaped body, dominated in its central part by explosion breccia and, in the marginal part, by tuff-breccia with an alkalic ultramafic rock cement. Their fragments consist mainly of sedimentary host rocks. Titanium nitride (osbornite) has thus been identified for the first time in terrestrial rocks, where it forms primary inclusions in corundum together with minerals such as native iron, iron silicides and a titanium-aluminum-zirconium phase that presumably belongs to the pseudobrookite group. Although the source rocks of the corundum are still unknown, its terrestrial origin is indisputable. The finds of titanium nitride and minerals in paragenesis with it indicate that corundum containing them as inclusions originated under specific, sharply reducing conditions similar to those under which individual stony meteorite types are formed.
Keywords: Devonian; Quaternary; Cenozoic::Quaternary; Paleozoic::Devonian; Палеозой::Девонская; Кайнозой::Четвертичная